Socioeconomic Status Disparities in Children's Cognition—Differences in Degree or Kind? - Hu, Lingyan; Farah, Martha J. (Perspectives on Psychological Science, 2026)
The "socioeconomic achievement gap" refers to socioeconomic disparities in children's academic outcomes. Do these gaps invariably reflect cognitive processes that are similar in kind across the socioeconomic status (SES) spectrum but differ quantitatively in their efficacy? Or, in some cases, do they reflect cognitive processes that differ, in kind, between higher and lower SES, that is, qualitatively? In this systematic review, we used the ways in which brain structure and function relate to cognitive performance to answer these questions, focusing on academically relevant cognitive abilities. Specifically, the brain correlates of performance served as a signal regarding the underlying cognitive processes used to perform cognitive tasks. The literature was searched for studies that reported whether SES moderated the brain–cognition relation. In 15 cases, significant moderation was found, suggesting that children from diverse SES backgrounds may use underlying brain systems differently to achieve cognitive task performance. Three general mechanisms are reviewed, as are the broader implications of qualitative differences for teaching and for the causal relations leading to socioeconomic disparities in cognition.